TAMI-70. METABOLIC VULNERABILITY TO GPX4 INHIBITION AND FERROPTOSIS OF QUIESCENT ASTROCYTE-LIKE GLIOMA CELL POPULATIONS. (12th November 2021) - Banu, Matei; Dovas, Athanassios; Argenziano, Michael; Zhao, Wenting; Higgins, Dominique; Upadhyayula, Pavan; Mahajan, Aayushi; Humala, Nelson; Nguyen, Trang; Zandkarimi, Fereshteh; Siegelin, Markus D; Brent, Stockwell; et al.
Abstract: Diversity is a key feature in the glioma ecosystem. Adaptation to a changing tumor microenvironment is achieved through cellular and metabolic plasticity. Here we show that slow-cycling, astrocyte-like glioma cell subpopulations activate distinct metabolic programs, rendering them susceptible to novel treatments. We performed multi-omics analysis on transgenic murine glioma models to characterize cellular heterogeneity. Bulk RNAseq on targeted time-dependent biopsies combined with scRNAseq uncovered distinct tumor cell populations, including a quiescent, astrocyte-like population relatively insensitive to conventional chemotherapy targeting proliferating cells. Using scRNAseq, we identified a persistently conserved astrocytic population in human IDH1-mt/wt high-grade gliomas. This astrocytic tumor population was more abundant in mouse models with constitutive Notch activation, however it was associated with alterations in several other transcriptional programs, suggesting that targeted therapies would likely be ineffective at eradicating it. Gene ontology analysis revealed enrichment in mitochondrial genes specifically regulating oxidative phosphorylation and tricarboxylic acid cycle. Energetic, lipidomic and metabolomic analyses revealed significant mitochondrial β-fatty acid oxidation and lipid catabolism, with less effective oxygen consumption rate and higher basal oxidative stress. Furthermore, this astrocytic tumor population had depleted levels of basal GSH and was more sensitive to reactive oxygen species. Leveraging this metabolic vulnerability, we performed drug screens and found that therapeutic inhibition of complex I or GPX4 was highly effective and synergistic. GPX4 inhibition induced ferroptosis, a newly-discovered form of programmed non-necroptotic cell death mediated by iron-driven lipid peroxidation. Using scRNAseq and RNAscope on ex vivo slice cultures from murine and human gliomas, we found that GPX4 inhibition and ferroptosis induction in the glioma microenvironment selectively eradicated the quiescent astrocytic subpopulation whereas proliferating glioma were less sensitive. Our data therefore supports a novel treatment paradigm, employing metabolic strategies, such as ferroptosis, in conjunction with chemotherapy and RT to target distinct tumor cell populations with different therapeutic vulnerabilities.